The Recent History and Current State of Autoethnography in Germany: A Literature Review - Anna Gonzalez Suero (Forum: Qualitative Social Research)
In German-speaking countries, autoethnography is viewed more critically and is less established than in English-speaking countries. The development of autoethnographic research in German-speaking countries has also only been reflected upon selectively. In my essay, I offer a broad overview of the development of autoethnographic practices by researchers at German universities. I have analyzed 97 explicitly autoethnographic texts published between 2007, the year of the earliest text I found, and 2024. I reviewed autoethnographies written in English and German from a range of disciplines, including art, sociology, religion, anthropology, geography, health sciences, and education. As part of my analysis, I identify the main characteristics and purposes of autoethnography in Germany. Through a comparison of the development of autoethnography in Spain and in the United States, I draw attention to the particularities of its use in Germany.